2019
DOI: 10.3762/bjoc.15.113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of aryl cyclopropyl sulfides through copper-promoted S-cyclopropylation of thiophenols using cyclopropylboronic acid

Abstract: The copper-promoted S-cyclopropylation of thiophenols using cyclopropylboronic acid is reported. The procedure operates under simple conditions to afford the corresponding aryl cyclopropyl sulfides in moderate to excellent yields. The reaction tolerates substitution in ortho-, meta- and para-substitution as well as electron-donating and electron-withdrawing groups. The S-cyclopropylation of a thiophenol was also accomplished using potassium cyclopropyl trifluoroborate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The reaction mixture was stirred at 120 °C for 48 h and afforded after chromatographic purification on SiO 2 (Hexanes/EtOAc, 100:1) 14o (15.0 mg, 83%) as a colorless oil: 1 H NMR (300 MHz, CDCl 3 ) δ 7.45–7.31 (m, 2H), 6.89–6.74 (m, 2H), 3.80 (s, 3H), 2.18 (tt, J = 7.4, 4.4 Hz, 1H), 1.04–0.93 (m, 2H), 0.74–0.59 (m, 2H); 13 C­{ 1 H} NMR (75 MHz, CDCl 3 ) δ 158.3, 130.1, 128.9, 114.6, 55.5, 14.2, 8.6. Characterization data matched the literature report …”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…The reaction mixture was stirred at 120 °C for 48 h and afforded after chromatographic purification on SiO 2 (Hexanes/EtOAc, 100:1) 14o (15.0 mg, 83%) as a colorless oil: 1 H NMR (300 MHz, CDCl 3 ) δ 7.45–7.31 (m, 2H), 6.89–6.74 (m, 2H), 3.80 (s, 3H), 2.18 (tt, J = 7.4, 4.4 Hz, 1H), 1.04–0.93 (m, 2H), 0.74–0.59 (m, 2H); 13 C­{ 1 H} NMR (75 MHz, CDCl 3 ) δ 158.3, 130.1, 128.9, 114.6, 55.5, 14.2, 8.6. Characterization data matched the literature report …”
Section: Methodssupporting
confidence: 79%
“…Characterization data matched the literature report. 27 4-((4-Methoxyphenyl)thio)tetrahydro-2H-pyran (14p). According to the general protocol B, to a solution of 5-chloro-1-aza-5stannabicyclo [3.3.3]undecane (100 mg, 0.340 mmol) in anhydrous THF (5.00 mL) was added (tetrahydro-2H-pyran-4-yl)magnesium chloride solution (3.36 mL, 1.68 mmol, 0.5 M in THF) under N 2 at 0 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Typical nucleophiles that were used in the Chan-Lam coupling with saturated boronic derivatives include azoles, [68,70,[152][153][154] primary and secondary amides, [155][156][157] anilines, [158] di-tert-butyl azodicarboxylate, [159] sulfoximines, [160] phenols, [153,158] carboxylic acids, [161] and thiophenols. [162] Again, as with the Suzuki-Miyaura reaction, most these reactions were performed with cyclopropyl or methyl boronic derivatives (see Table 5 for selected examples). For the former substrates, the method is especially useful since the corresponding products cannot be obtained from simple S N 2-type alkylations.…”
Section: C(sp 3 )-Heteroatom Bond Formation: Chan-lam Reaction and Related Methodsmentioning
confidence: 99%
“…[11][12][13] Among these, trivalent organobismuths such as triarylbismuths (Ar 3 Bi) have proved to be a kind of effective alternative arylating agents, supplanting the frequently used aryl halides and arylboronic acids, in coppermediated C-S cross-coupling reactions. [14][15][16][17] Recently, our group reported that copper pyrithione (bis(1-hydroxy-1H-pyridine-2-thionato-O,S)copper, CuPT) could act as both the coupling partner and copper center for C-S coupling reactions with aryl iodides and bromides as the arylating reagents. In this process, CuPT could be S-arylated smoothly under conventional heating (80 °C for ArI and 100 °C for ArBr) or microwave irradiation (110 °C for ArI and 130 °C for ArBr) with high yields and excellent functional group tolerance.…”
Section: Introductionmentioning
confidence: 99%